Features of Miscantus cultivation technology due to in vitro conditions - Пришляк, Р. І. (Problems of Environmental Biotechnology, 2018)
Some biological peculiarities of plants of the genus Miscanthus and conditions of their cultivation are considered. It has been proved that the in vitro cultivation of the miscanthus is ineffective and expedient for bioenergetics. Basic parameters for optimization of conditions for sterilization of explants and cultivation of the miscanthus plants were selected.